Tradisi Zikir dan Pengajian Kitab Turast Malam Kamis di Dusun Papringan - Maulana Iban Salda (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This paper examines the tradition of zikr and study of turats on Thursday nights in Papringan Village. This paper aims to examine the reception of the local community on the hadith about particular days so that the routine schedule of zikr in Papringan Village is held on Thursday night and not Friday night as is customary in the other locations. Furthermore, this paper examines the impact of zikr and the study of turats on the Papringan Village community. With interview techniques, this research shows that the reason for establishing Thursday night as a routine night of zikr and study of turats is because it has just happened (hereditary) and there is glory on Thursday, the day of forgiveness of sins. The reception of the results of zikr and study of turats was received quite well as evidenced by the conducive behavior of the local community (forming the good akhlaq of the community). However, tradition of zikr and study of turats on Thursday nights in Papringan Village not significantly contributes to the understandingof Islam.